Communicating authenticity in packaging of Korean cosmetics. (May 2019) - Lee, Sean; Sung, Billy; Phau, Ian; Lim, Aaron
Abstract: The purpose of this study is to explore the effect authenticity has on perceived value, attitude toward the product and purchase intention. A 3 (authenticity condition: indexical, iconic or control) by 2 (level of desire for existential authenticity: high vs. low) between-subjects factorial experimental design that comprised 6 cells was adopted in this study. The results revealed that perceived social and emotional value positively impacted on attitude toward the product which subsequently impacted on purchase intention for both authenticity conditions. Perceived quality was found to impact on attitudes only under the indexical authenticity condition. Perceived value dimensions were also found to have direct effects on purchase intention for both authenticity conditions with the exception of social value under the indexical condition. The findings suggest that authenticity plays an important role in influencing the social and emotional benefits which in turn influence attitudes and purchase intentions. Thus, managers will need to clearly highlighting these benefits when developing packaging for their products particularly for different age segments.